STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT SUKU MANDAR DI DESA SARUDE SARJO KABUPATEN MAMUJU UTARA SULAWESI BARAT - Rusmina H. Z.; Miswan Miswan; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2015)
The research entitled “Ethnobotanical Study of Plant Medicine on Mandarese Society in West Sulawesi Indonesia” has been carried out from April to June 2012 at the Sarjo, a village of Mandarese which is located in North Mamuju regency of West Sulawesi Province. The objective of the research was to collect data of medicinal plant species that used by the Mandarese people for their daily lives especially to ttreatment of various diseases and health maintenance. The basic data of medicinal plants has been collected by using direct interview to village leaders, religious leaders, traditional healers, and government officers These interviews were recorded with audio recorders and notebooks. Photographs were also taken to record information. All of plant materials used for this purpose collected in the field and then identified at the Herbarium Celebense (CEB) Tadulako University. The observation was included vernacular name, scientific name, family, habits, uses and technique and samples processing. Data analyzed by using formula of knowledge percentase analyzes of medicinal plants (Sunarno et al. 1991). The result showed that there were 50 (fifty) plants species belong to 28 families utilized as medicine. Zingiberaceae, Arecaceae, Solanaceae and Piperaceae were the dominant plant family were used by them. The organ of plants such as leaves, stems, roots, fruits, rhizomes and some were used as a whole or separately. Keywords: Plant medicine, Ethnobotany Study, Mandarese, Sarjo, West Sulawesi Indonesia